Commutativity between Base and Exponent

Let all the ordered pairs of distinct positive integer solutions of ( a , b ) (a,b) satisfying a b = b a a^b = b^a be ( a 1 , b 1 ) , ( a 2 , b 2 ) , , ( a n , b n ) (a_1, b_1), (a_2, b_2) ,\ldots , (a_n , b_n) .

Find i = 1 n ( a i + b i ) \displaystyle \sum_{i=1}^n (a_i + b_i) .


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

  • Note that if ( p , q ) (p,q) is a solution, then ( q , p ) (q,p) is also a solution to the equation a b = b a a^b=b^a .

  • None of a a and b b can be 1 1 .

  • Without the loss of generality, let a < b a<b .

  • a b a \mid b . Otherwise, a b 0 ≢ b a ( m o d a a^b\equiv 0 \not \equiv b^a (\mod a ).

  • Then a k = b ak=b , for some positive integer k 2 k\geq2 .

  • Now, a b = b a a a k = b a ( a k ) a = b a a k = b a^b=b^a \iff a^{ak}=b^a \iff (a^k)^a=b^a \iff a^k=b (As none of a k a^k and b b is 1 1 or 0 0 , and a 0 a\neq 0 ).

  • a k = b ak=b and a k = b a k = a k k = a k 1 a^k=b \implies ak=a^k \implies k=a^{k-1} (As a 0 a\neq 0 ).

  • So, k k 1 = a \sqrt[k-1]{k}=a

  • For k = 2 k=2 , a = k k 1 = 2 a=\sqrt[k-1]{k}=2 and b = a k = 4 b=ak=4 . ( 2 , 4 ) (2,4) and ( 4 , 2 ) (4,2) are solutions to the equation.

  • It can be proved by Induction on k k that

    For k 3 k\geq 3 , a k 1 > k a^{k-1}>k , with a 2 a\geq2 ;

which implies a k 1 k a^{k-1} \neq k \implies there are no more solution ( a , b ) (a,b) , other than ( 2 , 4 ) (2,4) and ( 4 , 2 ) (4,2) , to the equation a b = b a a^b=b^a .

So, ( 2 + 4 ) + ( 4 + 2 ) = 12 (2+4)+(4+2)=\boxed{12} is the answer.


Let's prove that for k 3 k\geq 3 , a k 1 > k a^{k-1}>k , with a 2 a\geq2 .

Induction Basis (IB) : For k = 3 k=3 , a k 1 = a 2 2 2 = 4 > k = 3 a^{k-1}=a^2\geq2^2=4>k=3 . So, for k = 3 k=3 , the claim holds.

Induction Hypothesis (IH) : Let's assume for some m 3 m\geq 3 , a m 1 > m a^{m-1}>m .

Inductive Step(IS) : a m 1 > m a m 1 × a > a m 2 m > m + 1 a^{m-1}>m \implies a^{m-1}\times a > am\geq2m>m+1 (As m 3 > 1 m\geq3>1 ) a m > m + 1 \implies a^m>m+1 . So, the claim holds for k = m + 1 k=m+1 provided it holds for k = m k=m .

Hence, By the Principle of Mathematical Induction, for k 3 k\geq 3 , a k 1 > k a^{k-1}>k , with a 2 a\geq2 . (Proved)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...